2018
DOI: 10.2478/psicolj-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Reversal Facilitates Contextual Conditioning in Rats’ Appetitive conditioning

Abstract: Two experiments were conducted with the goal of exploring the effect of experiencing associative interference upon concurrent learning about conditioned stimuli and contexts in rats' appetitive conditioning. During the first training phase, two groups of rats received a conditioned stimulus (CS1) followed by food, whereas another conditioned stimulus (CS2) was presented alone. During a second training phase, discrimination was reversed in group R, while it remained the same in group D. A new conditioned stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…In that sense, attention towards new stimuli may already be at an asymptote (Larrauri & Schmajuk, 2008), while attention to a familiar, irrelevant, context should be low and subject to increases with interference. Such an idea is consistent with the differential effects of the interference experience on new learning reported by Alcalá et al (2018). However, contrary to the experimental design used by Alcalá et al, (2018) in which animals only needed to learn to that the new cue was related to the administration of food, in the current experiments attention to the new cue was not enough to solve the spatial problem.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In that sense, attention towards new stimuli may already be at an asymptote (Larrauri & Schmajuk, 2008), while attention to a familiar, irrelevant, context should be low and subject to increases with interference. Such an idea is consistent with the differential effects of the interference experience on new learning reported by Alcalá et al (2018). However, contrary to the experimental design used by Alcalá et al, (2018) in which animals only needed to learn to that the new cue was related to the administration of food, in the current experiments attention to the new cue was not enough to solve the spatial problem.…”
Section: Discussionsupporting
confidence: 84%
“…As discussed earlier, Alcalá et al (2018) found no facilitation with a simple novel CS in Pavlovian conditioning following reversal training. We assumed that lack of effect to be due to a limit to which the reversal can increase attention to novel stimuli that already command substantial attention (Larrauri & Schmajuk, 2008).…”
Section: Methodsmentioning
confidence: 52%
See 3 more Smart Citations